Pembangunan Sistem Pengelolaan Data Nilai Siswa Berdasarkan Presensi Berbasis Web Dengan Fitur SMS Gateway Studi Kasus: SD Negeri Liprak Kidul 1 - Muhammad Sodiq; Tri Astoto Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
SD Negeri Liprak Kidul 1 is an elementary school located in Desa Liprak Kidul, Banyuanyar, Probolinggo. In order to manage its students scores, SD Negeri Liprak Kidul 1 is still not structured properly, they recorded all scores manually in score book which being held by each homeroom teacher. The student attendance is recorded in attendance book when the class begins. Beside that, parents have trouble with monitoring their children scores, because they only see the final scores when they accepting school report card on final semester. It caused the parents couldn't know the scores of the assignments, the quizzes and the exams of their children. To overcome these problems, a web-based students scores management system based on presence with SMS gateway feature is developed. This system is expected to help the process of managing students scores and also students attendance become easier. The system equipped with SMS getaway to make it easier for parents obtain information of their children scores and attendance. This system has been tested using white box testing for unit and integration testing, and black box testing for validation testing.